2023
DOI: 10.1101/2023.02.27.530352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microhomology-Mediated Circular DNA Formation from Oligonucleosomal Fragments During Spermatogenesis

Abstract: The landscape of extrachromosomal circular DNA (eccDNA) during mammalian spermatogenesis, as well as the biogenesis mechanism remains to be explored. Here, we revealed widespread eccDNA formation in human sperms and mouse spermatogenesis. We noted that germline eccDNAs are derived from oligonucleosomal DNA fragmentation in cells likely undergoing cell death. Interestingly, small-sized eccDNAs are associated with euchromatin, while large-sized ones are preferentially generated from heterochromatin. By comparing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(142 reference statements)
3
3
0
Order By: Relevance
“…In fact, our study also found that eccDNA is significantly abundant in the TE region, especially in the LTR region. Aligning with the findings reported by Hu et al 32 , our research also uncovered a significant correlation between eccDNAs and DNA Repeats within TEs. This observation suggests the possibility that DNA transposons may undergo circularization, either as an alternative to or concurrently with reintegration into the genome, a hypothesis that warrants further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, our study also found that eccDNA is significantly abundant in the TE region, especially in the LTR region. Aligning with the findings reported by Hu et al 32 , our research also uncovered a significant correlation between eccDNAs and DNA Repeats within TEs. This observation suggests the possibility that DNA transposons may undergo circularization, either as an alternative to or concurrently with reintegration into the genome, a hypothesis that warrants further exploration.…”
Section: Discussionsupporting
confidence: 91%
“…[8]; Third, by applying a permutation strategy, we showed that eccDNA-forming regions in the genome was depleted of long interspersed nuclear elements (LINEs) (enrichment score: 0.69; p value <10^-15) and was enriched, to a small extent, with short interspersed nuclear elements (SINEs) (enrichment score: 1.17; p value <10^-3). A similar observation was made in the eccDNAs isolated from mouse spermatogenetic cells [9]. Fourth, we identified enriched trinucleotide motif sequences flanking the start and end positions of sperm eccDNA molecules ( Figure 1D ).…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, such circular DNAs were also found in normal somatic cells and germline cells [7][8][9][10] and were termed eccDNA (extrachromosomal circular DNA) to be distinct from the ecDNAs in cancer cells. Contrary to ecDNAs, however, the biological functions and biogenesis mechanisms of eccDNAs are less studied, especially in the context of the human germline.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, sperm microDNAs could form during apoptosis, as demonstrated in some cell lines, 48 with eccDNA formation seemingly linked with fragments that are protected by nucleosomes rather than bound to protamines. 70 During sperm development, apoptosis can be triggered by failures of chromatin maturation in the testis or oxidative stress after spermiation. 71 Sperm with apoptotically fragmented DNA are the primary source of DNA breaks measured as sperm DNA fragmentation and are associated with poor fertility outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…seemingly linked with fragments that are protected by nucleosomes rather than bound to protamines 70. During sperm development, apoptosis can be triggered by failures of chromatin maturation in the testis or oxidative stress after spermiation.71Sperm with apoptotically fragmented DNA are the primary source of DNA breaks measured as sperm DNA fragmentation and are associated with poor fertility outcomes.71All subjects in the current study were young and healthy, with normal values of sperm DNA fragmentation (below 20%) determine if sperm microDNA levels correlate with DNA fragmentation or other indicators of sperm quality and fertility.More generally, we demonstrate that DS can detect candidate microDNAs without exonuclease enrichment, allowing for detection of mutations and putative microDNAs simultaneously.…”
mentioning
confidence: 99%